RNA-Seq and WGBS Analyses During Fruit Ripening and in Response to ABA in Sweet Cherry (Prunus avium) Reveal Genetic and Epigenetic Modulation of Auxin and Cytokinin Genes - Nathalie Kuhn; Macarena Arellano; Claudio Ponce; Christian Hodar; Francisco Correa; Salvatore Multari; Stefan Martens; Esther Carrera; José Manuel Donoso; Lee A. Meisel (Journal of Plant Growth Regulation, 2025)

Eco‐labeling of freight transport services: Design, evaluation, and research directions - Thomas Kirschstein; Arne Heinold; Martin Behnke; Frank Meisel; Christian Bierwirth (Journal of Industrial Ecology, 2022)
The idea of eco‐labeling is to provide customers with an easy‐to‐understand signal regarding the ecological impact of using a product or service. With this paper, we propose an eco‐labeling system for freight transportation. We discuss design options based on a common emission reporting standard and a related communication protocol. We further explain a procedure for deriving labels for shipments of goods and provide examples illustrating and evaluating the labeling process at selected land‐based freight transport services. Results indicate that eco‐labels can grade the environmental impact of a transport service reliably, even if heterogeneous goods are moved together. Finally, we outline challenges for future research associated with eco‐labeling in freight transportation markets.

Cardioembolic Ischemic Stroke Gene Expression Fingerprint in Blood: a Systematic Review and Verification Analysis - Teresa García-Berrocoso; Elena Palà; Marta Consegal; Benedetta Piccardi; Alex Negro; Natalia Gill; Anna Penalba; Hector Huerga Encabo; Israel Fernández-Cadenas; Andreas Meisel; Christian Meisel; Glen C. Jickling; et al. (Translational Stroke Research, 2020)

Discrimination of T-cell subsets and T-cell receptor repertoire distribution - Isabell Bretschneider; Michael J. Clemente; Christian Meisel; Manuel Guerreiro; Mathias Streitz; Werner Hopfenmüller; Jaroslav P. Maciejewski; Marcin W. Wlodarski; Hans-Dieter Volk (Immunologic Research, 2014)

Inadequate cytoplasmatic calcium signals in alveolar macrophages after cardiac surgery - Katharina Berger; Michael Sander; Anke Kohlar; Christian Meisel; Wolfgang Konertz; Thomas Volk (Inflammation Research, 2010)

Brain antigens in functionally distinct antigen-presenting cell populations in cervical lymph nodes in MS and EAE - Marloes van Zwam; Ruth Huizinga; Marie-José Melief; Annet F. Wierenga-Wolf; Marjan van Meurs; Jane S. Voerman; Knut P. H. Biber; Hendrikus W. G. M. Boddeke; Uta E. Höpken; Christian Meisel; Andreas Meisel; Ingo Bechmann; et al. (Journal of Molecular Medicine, 2009)

Association of MDR1 genotypes with susceptibility to colorectal cancer in older non-smokers - Elena Osswald; Andreas Johne; Gabriele Laschinski; Farhad Arjomand-Nahad; Uwe Malzahn; Julia Kirchheiner; Thomas Gerloff; Christian Meisel; Przemyslaw M. Mrozikiewicz; Jury Chernov; Ivar Roots; Karla Köpke (European Journal of Clinical Pharmacology, 2006)

Nucleocapsid protein of cell culture-adapted Seoul virus strain 80–39: Analysis of its encoding sequence, expression in yeast and immuno-reactivity - Jonas Schmidt; Burkhard Jandrig; Boris Klempa; Kumiko Yoshimatsu; Jiro Arikawa; Helga Meisel; Matthias Niedrig; Christian Pitra; Detlev H. Krüger; Rainer Ulrich (Virus Genes, 2005)

Role of platelet glycoprotein polymorphisms in cardiovascular diseases - Christian Meisel; Jos A. Lpez; Karl Stangl (Naunyn-Schmiedeberg's Archives of Pharmacology, 2004)